Medical-Grade Network Security - Air-Gap Isolation and PossibleWeak Points - Arendt, Daniel (Journal of Applied Computer Science, 2016)
Modern medical imaging devices (MID) are usually connected to the network. Transfer of digital data to the Picture Archiving and Communication Systems (PACS) and then to Hospital Information Systems (HIS) without the internal network is not technically nor economically reasonable. It is estimated that by the interconnection of medical devices and providing remote access to them, health care costs will be cut by 63 billion till 2030. Sharing MID’s over public network by remote access can dramatically cut costs of medical care but creates risks well known from oce networks. The firewall/IDS and the air gap isolation techniques are there applicable. Medical society ask for advice what to choose or what are the threats of network operation of medical devices. Here will be given description of known attacks on the security of air gapped networks and cases of disorder operation of systems and ecient data transfer from networks traditionally known as invulnerable and impermeable. Analyzing the presented cases of successful attacks allows to identify weak points of the air-gap mechanism. In conclusion opinion how to straighten security of isolated networks will be given, on the other hand an e ective IDS has advantage and many strong points.